A study on the survey and evaluation of indoor lighting environment and improvement of traditional raw earth dwellings in western Hunan Province - Shi, Lei; Zhang, Zhicheng; Zhang, Fupeng; Liu, Simian; Cao, Yang (Frontiers in Built Environment, 2025)
Due to the crystallization of regional culture and ecological wisdom, the quality of the lighting environment of traditional native dwellings in western Hunan directly affects the physical and mental health of older adult residents. Taking Laodong Village in Fenghuang County, western Hunan as an example, this study combines parametric modelling and simulation analysis to explore the key role of light environment on the improvement of ageing suitability with respect to natural lighting and passive lighting. The three-dimensional model is constructed using the Rhino-Grasshopper platform, and Ladybug tool is used to simulate the effects of different window sizes, positions and eave configurations on the indoor lighting, and optimization strategies are proposed based on the field research data. The study shows that the design of window openings with a sill height of 1.2 m, a horizontal center and a width of ≥1.5 m can significantly improve the illuminance and uniformity and in the passive technology, the reasonable layout of open tiles and skylights can supplement the natural light by more than 30%. The results of the study provide a scientific basis for traditional village renovation and a practical path for low-carbon sustainable rural construction.